Introduction: Political economy of food system transformation - Resnick, Danielle; Swinnen, Johan (International Food Policy Research Institute, 2023)
In August 2022, the Razoni cargo ship, laden with 26,000 tons of grain, navigated a narrow corridor of mined waters outside Ukraine’s port of Odessa. After Russia’s February 2022 invasion of Ukraine exacerbated rising food prices, threatening to plunge millions into hunger, the Razoni was the first ship allowed out of Ukraine under the UN-brokered Black Sea Grain Initiative. The ship’s journey symbolized the world’s dependence on grain from the Black Sea—which supplies 30 percent of the world’s wheat exports and constitutes the source of 12 percent of glob ally traded calories (Glauber and Laborde 2022)—and revealed the vulnerability of countries to dependence on concentrated supply sources (IPES 2022). More over, it underscored that food security and food systems are rarely the byproduct of agriculture policy alone but often intertwined with a broad set of political objectives. The impacts of the Ukraine war reverberated far and wide in 2022, amplifying weaknesses in many countries’ agricultural and food strategies and generating citizen demands for government accountability. From massive food protests in Tunisia that threatened the country’s fragile democracy to the siege of Ecuadorean cities by indigenous groups demanding more affordable food, global unrest reminded the world of the centrality of political economy to food systems at the international, national, and local levels.